Effect of a Self-Efficacy Enhancement Program on Capability of Trauma Patient Care on Scene and During Transfer by Emergency Medical Technician Personnel - Awae, Hisham; Khupantavee, Natenapha; Damkliang, Jintana (Journal of Research in Nursing-Midwifery and Health Sciences, 2020)
This research is a quasi-experimental study in a single group with repeated measures. The purpose of this study was to investigate the self-efficacy enhancement program on the capability of trauma patient care on scene and during transfer by emergency medical technician personnel. The sample was purposively selected, and thirty emergency medical technician personnel were included in this study. The self-efficacy enhancement program included attending the lecture with slide presentation, videos, role play, and practicing on the pre-hospital trauma patient care under supervision of the experts. Data were collected using and the observational checklist tool related to the practice for trauma patient care. The data were analyzed using paired t-test. The results showed that after receiving a self-efficacy enhancement program, the participants had a significantly higher level of practical skills for trauma patient care on scene and during transfer (t = -19.39, p <.001). When considering in each aspect of care, it was found that the level of practice skills increase in every aspect of care; including assessment, patient care on scene, immobilization and patient transfer. The study shows that the self-efficacy enhancement program can help to increase the ability of emergency medical technician personnel. As a result, the program should be used as a guideline for enhancing the performance of personnel working in emergency medical services in order to improve care for trauma patients effectively.